Investigation of the Impact Strength of the Epoxy-Polyester Material for Using in Aggressive Environments in the Water Transport - Serhii Yakushchenko; Mykola Brailo; Andriy Buketov; Anna Sapronova; Oleksandr Sapronov; Abdellah Menou (Communications - Scientific letters of the University of Zilina, 2021)
The influence of the aggressive environments of river water, seawater, oil petrol and sodium hydroxide on the impact strength of epoxy-polyester composite was investigated. Testing was conducted by two different methods. It was determined that the impact strength of specimens that were kept at air was W' = 4.2 kJ/m2 (by the second method - W'' = 7.0 kJ/m2). The energy spent on destruction of the control specimen was E = 0.92 J. The main regularities of the crack propagation process in the studied material were found and qualitatively described. The time of a crack propagation (τ = 0.16 μs) was determined. The maximum load, which leads to destruction of the specimen was P max = 2.47 kN. The comparative analysis of investigated specimens was conducted by the IR-spectroscopy method. It was found, that the biggest decrease in material properties was observed for the specimen that was kept in the petrol environment.